Titin and Troponin: Central Players in the Frank-Starling Mechanism of the Heart - Fukuda, Norio; Terui, Takako; Ohtsuki, Iwao; Ishiwata, Shin'ichi; Kurihara, Satoshi (Current Cardiology Reviews, 2009)
The basis of the Frank-Starling mechanism of the heart is the intrinsic ability of cardiac muscle to produce greater active force in response to stretch, a phenomenon known as length-dependent activation. A feedback mechanism transmitted from cross-bridge formation to troponin C to enhance Ca2+ binding has long been proposed to account for length-dependent activation. However, recent advances in muscle physiology research technologies have enabled the identification of other factors involved in length-dependent activation. The striated muscle sarcomere contains a third filament system composed of the giant elastic protein titin, which is responsible for most passive stiffness in the physiological sarcomere length range. Recent studies have revealed a significant coupling of active and passive forces in cardiac muscle, where titin-based passive force promotes cross-bridge recruitment, resulting in greater active force production in response to stretch. More currently, the focus has been placed on the troponin-based “on-off” switching of the thin filament state in the regulation of length-dependent activation. In this review, we discuss how myocardial lengthdependent activation is coordinately regulated by sarcomere proteins.
Keywords: cardiac muscle